Statistical physics of biomolecules : an introduction - Zuckerman, Daniel M. (CRC Press/Taylor & Francis, 2010)
Proteins Don't Know BiologyPrologue: Statistical Physics of Candy, Dirt, and Biology Guiding Principles About This Book Molecular Prologue: A Day in the Life of Butane What Does Equilibrium Mean to a Protein? A Word on Experiments Making Movies: Basic Molecular Dynamics Simulation Basic Protein Geometry A Note on the Chapters The Heart of It All: Probability Theory Introduction Basics of One-Dimensional Distributions Fluctuations and Error Two+ Dimensions: Projection and Correlation Simple Statistics Help Reveal a Motor Protein's Mechanism Additional Problems: Trajectory Analysis Big Lessons from Simple Systems: Equilibrium Statistical Mechanics in One DimensionIntroduction Energy Landscapes Are Probability Distributions States, Not Configurations Free Energy: It's Just Common Sense If You Believe in Probability Entropy: It's Just a Name Summing Up Molecular Intuition from Simple Systems Loose Ends: Proper Dimensions, Kinetic Energy Nature Doesn't Calculate Partition Functions: Elementary Dynamics and Equilibrium Introduction Newtonian Dynamics: Deterministic but Not Predictable Barrier Crossing-Activated Processes Flux Balance: The Definition of Equilibrium Simple Diffusion, Again More on Stochastic Dynamics: The Langevin Equation Key Tools: The Correlation Time and Function Tying It All Together So Many Ways to ERR: Dynamics in Molecular Simulation Mini-Project: Double-Well Dynamics Molecules Are Correlated! Multidimensional Statistical Mechanics Introduction A More-Than-Two-Dimensional Prelude Coordinates and Force Fields The Single-Molecule Partition Function Multimolecular Systems The Free Energy Still Gives the Probability Summary From Complexity to Simplicity: The Potential of Mean Force Introduction: PMFs Are Everywhere The Potential of Mean Force Is Like a Free Energy The PMF May Not Yield the Reaction Rate or Transition State The Radial.